2017
DOI: 10.1159/000458769
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Consumption of Artificial Sweetener in Packets or Tablets and Type 2 Diabetes Risk: Evidence from the E3N-European Prospective Investigation into Cancer and Nutrition Study

Abstract: Background: The influence of artificial sweeteners on metabolic diseases is controversial. Artificially sweetened beverages have been associated with an increased risk of type 2 diabetes (T2D) but biases and reverse causation have been suspected to have influenced the observed association. In addition, it has been suggested that investigation into the relationship between the frequency and duration of the consumption of packet or tablet artificial sweeteners and T2D risk is necessary. Methods: We used data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…A few large prospective cohort studies98 99 100 101 102 with long term follow-up investigated the association between NSS intake and different health outcomes. However, the NSSs being investigated were not sufficiently specified to match the inclusion criteria of this review.…”
Section: Discussionmentioning
confidence: 99%
“…A few large prospective cohort studies98 99 100 101 102 with long term follow-up investigated the association between NSS intake and different health outcomes. However, the NSSs being investigated were not sufficiently specified to match the inclusion criteria of this review.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies investigating the exposure to AS, 2 prospective cohort studies [ 162 , 163 ] and one case-control study [ 164 ] described an increased risk of type-2 diabetes, while 2 prospective [ 160 , 165 ] and 1 retrospective cohort studies [ 166 ] found no association between AS consumption and risk of diabetes. There were no studies investigating diabetes risk in association with NNCS consumption.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that higher LCSB consumption is not associated with adverse associations with prediabetes diagnostic markers or a glycemic response compared to plain water. Fagherazzi et al [ 33 ] reported that both a high frequency and a longer consumption period of LCS in packages or tablets was independently associated with type 2 diabetes risk in a European prospective cohort of women, but that the risk was partially mediated by adiposity. These results differ from those found in our study in several ways.…”
Section: Discussionmentioning
confidence: 99%